2021
DOI: 10.2196/27063
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in Public Awareness About BRCA and Genetic Testing in Prostate Cancer: Social Media Landscape Analysis

Abstract: Background Genetic testing, particularly for BRCA1/2, is increasingly important in prostate cancer (PCa) care, with impact on PCa management and hereditary cancer risk. However, the extent of public awareness and online discourse on social media is unknown, and presents opportunities to identify gaps and enhance population awareness and uptake of advances in PCa precision medicine. Objective The objective of this study was to characterize activity and e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…awareness surrounding hereditary cancer testing on social media platforms has identified that the topic of prostate cancer results in significantly less public engagement when compared to breast cancer. 20,21 We believe that the reasons surrounding this delayed adoption of guidelines at our own institution are most likely multifactorial and in line with barriers encountered at other academic institutions (i.e., implementation barriers, provider variability, and patient factors, etc. ).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…awareness surrounding hereditary cancer testing on social media platforms has identified that the topic of prostate cancer results in significantly less public engagement when compared to breast cancer. 20,21 We believe that the reasons surrounding this delayed adoption of guidelines at our own institution are most likely multifactorial and in line with barriers encountered at other academic institutions (i.e., implementation barriers, provider variability, and patient factors, etc. ).…”
Section: Discussionmentioning
confidence: 88%
“…[20][21][22][23] Other institutions have encountered lack of physician knowledge regarding testing availability, skepticism about the evidence supporting practice guidelines, and cost as primary factors. 20,21 Other work assessing | 521…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, public metadata for hereditary cancer communities on Facebook consist of about 73 groups ranging in size from 36 to 13,000 people. 1 Out of this population, 3 of the 10 participants were active administrators of at least one Facebook support group for breast cancer. All participants were a member of at least one breast cancer support group over a time period between 2008 and 2021.…”
Section: Data and Code Availabilitymentioning
confidence: 99%
“…More recently, we found substantially less engagement on Twitter, Facebook, and YouTube about BRCA and genetic testing in prostate cancer compared with breast cancer. 15 These analyses can provide insights into public awareness about different topics and potential strategies for health communication campaigns.…”
Section: Observational Studies Using Social Mediamentioning
confidence: 99%